THE IMPACT OF MOBILE ASSISTED LANGUANGE LEARNING (MALL) SMARTPHONE’S APPLICATION: A DESIGN-BASED STUDY - Jakob, Juvrianto Chrissunday; Leatemia, Meiti (Epigram, 2024)
Mobile Assisted Language Learning (MALL) is a method for enhancing language teaching methods autonomously, utilizing language learning apps conveniently and flexibly. Engaging and interactive learning methods, such animation, images, and audio, can effectively communicate knowledge and enhance memory retention by being easily comprehensible and stimulating human senses. Innovative solutions are required to address the challenges of limited access, flexibility, and pedagogical assistance in Distance Education. This study utilizes the Design Based Research (DBR) technique to create Mobile Technology, a mobile application tailored for vocabulary acquisition. The development process consists of cycles of design, execution, and evaluation, emphasizing the requirements and environment of the learner. The implementation of VocUp Mobile Technology was successful and proven its efficiency in enhancing vocabulary proficiency. This program facilitates interactive and adaptable learning by incorporating elements that respond to user requirements and learning circumstances. Mobile technology has enhanced vocabulary acquisition by offering a more adaptable and convenient approach, addressing common obstacles in distance education. This facilitates the adoption of advanced and student-focused learning methods. This Mobile Technology provides a practical and efficient answer for vocabulary acquisition issues in a university setting, particularly in Distance Education. This program enhances language skills and promotes the creation of flexible and all-encompassing learning methods through its responsive and educational approach.